Rural maternal mortality ratio in China - You, Hua; Bogg, Lennart; Costa, Ayesha De; Dong, Hengjin (The lancet. Global health, 2014)
A recent letter to The Lancet1 drew attention to Chinese achievements with regard - to Millennium Development Goals (MDGs) 4 and 5. The wide wealth and health disparities, - including in maternal survival, in China, linked both to the urban-rural divide and - to the east-west divide, have been noted many times.2,3 Here we draw attention to - the closing gap between urban and rural maternal mortality ratio (MMR), both in terms - of the drivers behind the dramatic drop in rural maternal mortality and the surprising - lack of improvement in urban maternal mortality.
Gesehen am 21.09.2020